Aerobic exercise training alleviates renal injury in db/db mice through inhibiting Nox4-mediated NLRP3 inflammasome activation - Zhou, Zhongyuan; Ying, Changjiang; Zhou, Xiaoyan; Shi, Yuanyuan; Xu, Jian; Zhu, Yandong; Wang, Meng; Li, Yan; Li, Xiaofei; Xiang, Jie (Experimental gerontology, 2022)
Diabetic kidney disease (DKD) is the leading cause of end-stage renal disease, with few therapeutic options available to slow its progression. Aerobic exercise training is an effective strategy for diabetes mellitus and its complications' prevention and treatment. The purpose of this study was to determine the effects of aerobic exercise training on diabetic kidney injury in db/db mice and to characterize the mechanism underlying the renal protective effects. The db/db mice were exercised 5 days a week for 60 min each day for 8 weeks at a speed of 5.6 m/min, after which renal function, morphology, oxidative stress, inflammation, fibrosis, and the expression of the Nox4/ROS/NF-κB/NLRP3 signaling pathway-related protein were assessed. Our results showed that aerobic exercise training significantly reduced body weight and microalbuminuria, improved renal function, and attenuated renal pathological changes in db/db mice independent of hyperglycemic state. Aerobic exercise training was also found to significantly improve oxidative stress and inflammation in the kidneys of db/db mice by decreasing the activity of complex I, the levels of MDA, 8-OHdG, Nox4, ROS, TNF-α, MCP-1, IL-6, and IL-18, increasing the activities of SOD and GSH-Px, the expression of klotho and NPHS2, and decreasing the phosphorylation of NF-κB p65 and IκBα, as well as the expression of NLRP3, ASC, caspase-1 p20, and IL-1β. Additionally, aerobic exercise training decreased TGF-β, collagen I, collagen IV, and α-SMA expression, thereby slowing the progression of kidney fibrosis in db/db mice. In conclusion, aerobic exercise training effectively reduces oxidative stress, inflammation, and renal fibrosis by modulating the Nox4/ROS/NF-κB/NLRP3 signaling pathway, implying that aerobic exercise training has significant potential to protect diabetic kidney injury and should be given more emphasis in DKD treatment. •Exercise alleviates high glucose-induced renal injury in db/db mice.•Exercise improves glomerular ultrastructure in db/db mice.•Exercise suppresses Nox4 expression and subsequently inhibits ROS over-production.•ROS over-generation activates NLRP3 inflammasome.